Comparison of attitude towards biodiversity and willingness to participate in sustainable palm oil certification between independent and organized smallholders in Peninsular Malaysia - Mohd Esa, Shakinah (2016)
Oil palm plantations are often considered to be the cause of the destruction of forests. Owner of the plantation should take into account towards biodiversity conservation in their farmland to change the perception. This study was conducted to compare the attitude smallholders on biodiversity in oil palm farm and their willingness of sustainable palm oil certification in Peninsular Malaysia between independent and organized oil palm smallholders. Since this study was a pilot project, two groups of smallholders in Peninsular Malaysia are assessed to provide baseline data reflecting the attitude towards biodiversity and willingness in sustainable oil palm. Data were collected from 300 respondents by using semi-structured method and representative of all smallholders in Peninsular Malaysia. However, the results of this study may have implications for other groups on a practical basis. Organized smallholders have more awareness about biodiversity concepts, compared independent smallholders. However, independent smallholders are willing to increase biodiversity in oil palm farm than organized smallholders. Overall, respondents had the most positive perception about the biodiversity concept and were the least positive about the sustainable palm oil certification.